Explore IDNLearn.com's extensive Q&A database and find the answers you need. Ask any question and receive comprehensive, well-informed responses from our dedicated team of experts.
Sagot :
Answer:
[tex]f(x) - g(x) = 2x + 12[/tex]
[tex]m(x) = f(x) - g(x)[/tex] --- True
Step-by-step explanation:
Given
[tex]f(x) = -3x + 5[/tex]
[tex]g(x) = -5x - 7[/tex]
[tex]m(x) = 2x + 12[/tex]
Solving (a): [tex]f(x) - g(x)[/tex]
From the given parameters, we have:
[tex]f(x) = -3x + 5[/tex]
[tex]g(x) = -5x - 7[/tex]
So:
[tex]f(x) - g(x)=-3x+5 + 5x + 7[/tex]
Collect like terms
[tex]f(x) - g(x) = 2x + 12[/tex]
Solving (b) m(x) = f(x) = g(x)?
In (a), we have:
[tex]f(x) - g(x) = 2x + 12[/tex]
And
[tex]m(x) = 2x + 12[/tex] --- given
By comparison:
[tex]m(x) = f(x) - g(x)[/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to assisting you again.